Cross-cultural adaptation of the Turkish version of the dentin hypersensitivity experience questionnaire short form (DHEQ-15) - Gizem Ayan; Tugba Misilli; Mehmet Buldur (BMC Oral Health)
Abstract Background The short form of the Dentin Hypersensitivity Experience Questionnaire (DHEQ-15) is a valid and reliable tool for Oral Health-Related Quality of Life (OHRQoL) studies. The aim of this study was cross-culturally adapt and validate the English version of DHEQ-15 for the Turkish language. Methods The Turkish version of the DHEQ-15 was developed using the forward-backward translation method. Two independent translators translated it from English to Turkish, followed by back-translation into English. A pilot study was conducted with 30 patients with dentin hypersensitivity (DH). The sample consisted of 150 individuals with DH and 150 without. DH was assessed using the Schiff Sensitivity Scale by applying air to the cervical area of the tooth for 1 s from a distance of 1 cm. A total of 300 individuals completed the Turkish DHEQ-15 in the waiting room. Subsequently, 30 randomly selected individuals with DH completed the questionnaire again after 7–10 days to assess test-retest reliability. Participants provided an overall oral health rating assessment on a 6-point scale. The reliability of the DHEQ-15 was assessed using internal consistency and test-retest methods. Exploratory Factor Analysis (EFA) identified its domains, while construct validity was evaluated through cross-cultural (Confirmatory Factor Analysis- CFA), discriminative (Mann-Whitney test) and convergent (Spearman correlation) validity. Results The demographic characteristics of the sample included 137 men and 163 women, with an average age of 36. The Turkish DHEQ-15 demonstrated excellent internal consistency (α = 0.970) and outstanding test-retest reliability (r = 0.920, p < 0.001), indicating an excellent correlation. Confirmatory factor analysis confirmed the unidimensional scale structure of the Turkish DHEQ-15 (p = 0.000). A statistically significant negative correlation was found between the DHEQ-15 score and the overall oral health rating assessment (p < 0.05). Participants with DH had a significantly higher DHEQ-15 score compared to those without DH (p < 0.001). Conclusions This study provides evidence supporting the cross-cultural validity and reliability of the Turkish DHEQ-15.